Perlindungan Hukum Data Nasabah Dalam Bank Digital Berbasis General Data Protection Regulation Di Indonesia - Affan Najmun Nahar; Putra Bagus Oktavian; Adrian Hadiputra; Dismas Arya Diputra; Ahmad Rezal Rizkyansyah; Baidhowi (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Advances in digital technology have driven the transformation of banking services from conventional systems to digital banks that rely on electronic data processing. This transformation brings convenience to customers, but at the same time increases the risk of personal data breaches, unauthorized access, and cyberattacks. This study aims to analyze legal regulations governing digital banks regarding customer data breaches,legal protections for customer data, and to compare regulations in Indonesia with the General Data Protection Regulation (GDPR) in the European Union. The research methodology employed is a normative legal approach using legislative, conceptual, and comparative analyses. The research results indicate that Indonesia already has a legal framework for customer data protection through the principle of bank secrecy in the Banking Law, the Information and Electronic Transactions Law, and the Personal Data Protection Law, which require data controllers to ensure data security and report data protection failures within a maximum of 3 x 24 hours. However, the implementation of such protection still faces challenges in the areas of supervision, compliance, and enforcement. Compared to the GDPR, regulations in Indonesia still lag behind in terms of accountability, the severity of sanctions, the obligation to notify data breaches, and the authority of the supervisory body. Therefore, legal protection of customer data in digital banks in Indonesia needs to be strengthened through supervision